Reheated Palm Oil Consumption And Risk Of Atherosclerosis: Evidence At Ultrastructural Level - Tan Kai Xian; Noor Azzizah Omar; LowWen Ying; Aniza Hamzah; Santhana Raj; Kamsiah Jaarin; Faizah Othman; Farida Hussan (Hindawi Publishing Corporation, 2024)
Non-Indexed Publication